Personality traits and the digital entrepreneur: Much of the same thing or a new breed?. Issue 2 (2nd April 2020) - Bandera, Cesar; Passerini, Katia
ABSTRACT: The impact of young companies with purely digital products and services has raised interest in so-called digital entrepreneurs (DEs), all-digital business models, and ecosystems in which DEs thrive. Researchers study this Schumpeterian destruction, policy makers try to replicate digital ecosystems, and investors seek the next "gazelle." We return to an early research topic: can psychological traits classify entrepreneurs? Are DEs unique digital natives, or are they business as usual? Using the five-factor personality model and psycholinguistic analysis of entrepreneur interviews, we improve start-up performance prediction when distinguishing DEs from traditional entrepreneurs. DEs are less concerned about the future than traditional entrepreneurs and use "neuroticism" to their advantage. Anxiety in DEs correlates with performance, whereas anxiety correlates with risk and negatively with performance among traditional entrepreneurs. We show that DEs are sufficiently different from traditional entrepreneurs to warrant further research on their motivation and on policies and ecosystems that reflect these differences.